2020
DOI: 10.14254/2071-8330.2020/13-4/16
|View full text |Cite
|
Sign up to set email alerts
|

Institutions, economic openness and credit cycles: An international evidence

Abstract: This study aims at investigating the influence of institutions and economic openness on credit cycles in a global sample. Six institutional quality indicators combined with net inward FDI and trade openness are collected to estimate, respectively, the effects of institutions and economic openness on credit cycles. Our panel data covers 60 economies, including 32 low-and middle-income economies (LMEs) and 28 high-income economies (HIEs), the data ranging between 2003 and 2017. Although better institutions tend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…This implies that institutional quality (economic freedom) is essential for real GDP growth in SSA. This result of our study is consistent with the work of [ 56 , 65 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This implies that institutional quality (economic freedom) is essential for real GDP growth in SSA. This result of our study is consistent with the work of [ 56 , 65 ].…”
Section: Resultssupporting
confidence: 94%
“…[ 56 ] Observed that institutions enhance credit growth and in turn economic growth in the panel data of 60 countries for the study periods of 2003 and 2017. Similarly [ 57 ], examined the effect of institutional quality on economic growth.…”
Section: Reviews Of Related Literaturementioning
confidence: 99%
“…While institutions were traditionally associated with organizational functions, the contemporary view broadens the concept to include technology, influencing economic growth as an endogenous variable. Enhancements in institutional quality are linked to increased productivity [ 26 ] exhibiting a positive impact on economic growth [ 27 , 28 ]. The evolution of institution is crucial for long-term growth, with static institutions having short-term effects but lacking long-term impacts [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 56 ] found institutional quality in African countries from the period of 1999–2017 through the use of the FMOLS estimation technique. Further, their study found that there is bidirectional causality between economic growth and institutional quality [ [57] , [58] ]. Observed that institutions enhance credit growth and in turn economic growth in the panel data of 60 countries for the study periods of 2003 and 2017.…”
Section: Reviews Of Related Literaturementioning
confidence: 99%